A new Western Disturbance Index for the Indian winter monsoon - Midhuna, T M; Kumar, P; Dimri, A P (Journal of Earth System Science, 2020)
The Himalayas are storehouse of freshwater, which is of utmost importance for agriculture and power generation for billions of people in India. Winter (December, January and February: DJF) precipitation associated with Western Disturbances (WDs) influences Himalayan climate, glaciers, snow-water storage, etc. One-third of annual precipitation over northern Indian region is received during winter. Winter WDs are synoptic-scale systems embedded the subtropical westerly jet (SWJ). Their orographic interaction with the Himalayas intensifies precipitation over Pakistan and northern India. Precipitation due to WDs and associated dynamics are termed as Indian winter monsoon (IWM). The present study focuses on the WDs climatology using National Center for Environmental Prediction/National Center for Atmospheric Research, US (NCEP/NCAR) reanalysis data. The period of study spans over 29 years (1986–2016) during which ~500 WDs were observed as per India Meteorological Department (IMD) daily weather report. Precipitation, vertical distribution of wind and geopotential height during the passage of these WDs are analyzed. Importantly, a new index, Western Disturbance Index (WDI), for measuring strength of IWM is proposed by using difference of geopotential height at 200 and 850 hPa levels. The index is able to capture changes in 500 hPa wind, air temperature and mean sea level pressure during the passage of WDs.